A comparison of the electrocortical response to monetary and social reward. Issue 3 (24th January 2018) - Distefano, Amanda; Jackson, Felicia; Levinson, Amanda R; Infantolino, Zachary P; Jarcho, Johanna M; Nelson, Brady D
Abstract: Affective science research on reward processing has primarily focused on monetary rewards. There has been a growing interest in evaluating the neural basis of social decision-making and reward processing. The present study employed a within-subject design and compared the reward positivity (RewP), an event-related potential component that is present following favorable feedback and absent or reduced following unfavorable feedback, during monetary and social reward tasks. Specifically, 114 participants (75 females) completed a monetary reward task and a novel social reward task that were matched on trial structure, timing, and feedback stimuli in a counterbalanced order. Results indicated that the monetary and social RewP were of similar magnitude, positively correlated and demonstrated comparable psychometric properties, including reliability and dependability. Across both the monetary and social tasks, women demonstrated a greater RewP compared with men. This study provides a novel methodological approach toward examining the electrocortical response to social reward that is comparable to monetary reward.